Valuation of Tatry mountain resorts, a.s. - Senčar, Simon (2024)
This thesis presents, via a flexible valuation model, a comprehensive analysis of the economic viability of Jasná, a leading ski resort in Slovakia, within the broader context of climate change and its impacts on the ski industry. Employing a Discounted Cash Flow (DCF) model, the paper evaluates the resort's financial outlook amidst evolving environmental challenges. The research encompasses a detailed review of current climate trends, their direct effects on ski tourism, particularly regarding snow availability, and subsequent adaptations such as artificial snow production. Key findings indicate that major resorts like Jasná may remain economically viable and competitive due to their advanced snowmaking technologies, diversified business operations, and effects such as temporal or spatial substitution. Our findings indicate that the standard two-phase DCF model might not be appropriate for the ski industry due to its going concern assumption, thus and the single-phase investment-adjusted DCF model suggests a valuation of EUR 72 – 91 million for Jasná.